Harriet Backer - Every atom is colour - Bierlich, Emilie Boe 1979-; Bø, Ragnhild M. 1975-; Dalåsen, Vilde 1989-; Hansen, Vibeke Waallann 1970-; Haugsbø, Tove Kårstad 1984-; Lerberg, Ellen 1964-; Liu, Mirjam 1981-; Rech, Carina 1987- (Hirmer, 2023)
Harriet Backer (1845–1932) was one of Norway’s most prominent painters of the 19th century and a pioneer among women artists in Europe. In 1880, she debuted in the Paris Salon and lived in Munich and Paris. Back in Oslo, she established a successful school for painters. This catalogue presents Backer to an international audience, thus giving her back the place she deserves in art history
Impressum: "The catalog is published in connection with the exhibition "Harriet Backer. Every Atom is Colour" ... exhibited at The National Museum of Art, Architecture and Design, Oslo, 29 September 2023 - 14 January 2024; Nationalmuseum, Stockholm, 22 February - 18 August 2024; Musée d'Orsay, Paris, 24 September 2024 - 11 January 2025; Kode Art Museums and Composer Homes, Bergen, 21 February - 15 June 2025"
Keywords: Backer, Harriet -- 1845-1932; Geschichte 1874-1878; Malerei; Studium; München; Foreign languages; Kunst 20. Jahrhundert; Malerei 19. Jahrhundert; Malerei 20. Jahrhundert; Künstlermonographien; 18./19. Jahrhundert; 20. Jahrhundert; Art 20th Century; Painting 19th Century; Painting; Painting 20th Century; Arts; Artist monography; 18th/19th Century; 20th Century; Ausstellungskatalog -- KODE -- 21.02.2025-15.06.2025 -- Bergen, Norwegen; Ausstellungskatalog -- Kode Art Museums and Composer Homes -- 21.02.2025-15.06.2025 -- Bergen; Ausstellungskatalog -- Musée d'Orsay -- 24.09.2024-11.01.2025 -- Paris; Ausstellungskatalog -- Nasjonalmuseet for Kunst, Arkitektur og Design -- 29.09.2023-14.01.2024 -- Oslo; Ausstellungskatalog -- Nationalmuseum -- 22.02.2024-18.08.2024 -- Stockholm; Ausstellungskatalog -- The National Museum of Art, Architecture and Design -- 29.09.2023-14.01.2024 -- Oslo